THE ROLE OF THE MADRASAH HEADMASTER IN IMPLEMENTING MEETING MANAGEMENT - Chotimah, Chusnul; Fauzi, Moh Ali; Miftahuddin, Miftahuddin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to determine the role of the Madrasa headmaster in implementing meeting management, the obstacles faced, and the factors that influence the implementation of meeting management at MAN 1 Nganjuk. This research is qualitative research using data collection techniques through observation and interviews. The results of the research show that the headmaster of MAN 1 Nganjuk implements four roles in implementing meeting management, namely as Leader, Manager, Motivator, and Supervisor. The obstacles faced by the head of MAN 1 Nganjuk in implementing meeting management included: the absence of several meeting participants, lack of focus from meeting participants, as well as conflict and tension between meeting participants. Apart from that, several factors influence meeting management at MAN 1 Nganjuk, such as meeting objectives, meeting preparation, effective communication, effective leadership, evaluation and follow up.